Problematika Kesetaraan Akses Dalam Pendidikan Di SD Negeri Lingkok Bunut Kabupaten Lombok Tengah - Nurhasanah; Evi Zuyyina; Donita Filiyanti N.; Basilius Redan Werang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Equality of access to education is one of the main principles in sustainable human resource development. Equal education provides every individual with the opportunity to obtain educational services without discrimination based on economic status, gender, geographic location, physical condition, or socio-cultural background. However, reality shows that various obstacles still exist that cause unequal access to education in various regions. This article analyzes the problem of equal access to education at SDN Lingkok Bunut, Janapria District, Central Lombok Regency. The methods used are literature study and descriptive analysis of the condition of basic education in rural areas. The results of the study indicate that several factors influence equal access to education, namely limited facilities and infrastructure, family socio-economic conditions, access to information technology, and the quality of educational services. In addition, geographic location and limited learning resources also pose obstacles to equal access to education. Therefore, synergy is needed between the government, schools, communities, and parents to improve the quality and equal access to education for all students.